The effect of sodae herbal capsule on migraine headaches - Mansour Rezaei; Daryoush Afshari; Negin Fakhri (Institue of Medicinal Plants, ACECR, 2020)
Background: Migraine is a common neurobiological disorder and various methods have been proposed for its treatment, including herbal remedies. Sodae is an herbal capsule produced and marketed by "Booali Daroo" Pharmaceutical Company, based on Iranchr('39')s traditional medicine, in compliance with the instructions of the Food and Drug Administration of Iran and with a license issued by this administration of the Ministry of Health. Objective: The present study was conducted to compare the effects of Sodae and placebo capsules on migraine headaches. Methods: This clinical trial (2017-18) was conducted on 74 migraine patients (based on the International Headache Society definition) in Kermanshah, who was randomly divided into two groups. The intervention and placebo groups received 720 mg Sodae and the Avesil capsules for three months, respectively. Headache characteristics were measured using the Migraine Disability Assessment (MIDAS) and Headache Impact Test-6 (HIT-6). Data were analyzed in SPSS-25 using Mann-Whitney's and Chi-square tests and the Repeated Measures ANOVA. 116  Results: The headache characteristics reduced significantly more in the intervention group. Compared to the placebo group, the amount of reduction was higher in the intervention group in the frequency (3.53 ± 0.64 vs. 1.79 ± 0.35; P = 0.041), the severity (1.81 ± 0.14 vs. 1.10 ± 0.13; P = 0.001) and the duration of attacks (3.05 ± 0.66 vs. 1.35 ± 0.31; P = 0.012). MIDAS and HIT scores were further reduced in the drug group than the placebo group. Nonetheless, no significant differences were observed between the two groups in terms of side-effects (P = 0.486). Conclusion: According to the results, Sodae capsule is significantly more effective than placebo in reducing headache characteristics, and given its limited side-effects, it is recommended for the treatment of migraines.